Scanning laser terahertz near-field reflection imaging system. (30th October 2019) - Okada, Kosuke; Serita, Kazunori; Zang, Zirui; Murakami, Hironaru; Kawayama, Iwao; Cassar, Quentin; Macgrogan, Gaëtan; Guillet, Jean-Paul; Mounaix, Patrick; Tonouchi, Masayoshi
Abstract: We developed a scanning laser terahertz (THz) near-field reflection imaging system using a fiber-coupled femtosecond laser source for high spatial resolution measurements without any sub-wavelength probes. In this system, THz wave pulses generated at the laser focusing spot in a non-linear optical crystal interact with a sample set on the crystal. Using this system, we obtained the THz reflection images of metallic structures with a resolution of ∼ λ THz /34 ( λ THz = 680 μ m) and also observed paraffin-embedded human breast tissue of several 10 μ m in size. These results promise that this system can be suitable for industrial applications which require micron-scale resolution.